MEWUJUDKAN MASYARAKAT BERKARAKTER PEDULI LINGKUNGAN MELALUI PROGRAM ADIWIYATA - Mirza Desfandi (Sosio-Didaktika: Social Science Education Journal, 2015)
This article aims to provide an effort to educate and inform the public about environmental issues become more critical. Develop community character can effectively care for the environment is possible through environmental education in schools. As a place of learning, the school has a special role to play; schools can help students to understand the impact of human behavior on Earth. Adiwiyata program implemented in order to realize the school community who are responsible for the protection and management of the environment through good school governance to support sustainable development. Adiwiyata program combines learning and action, so as to provide an effective method to change behavior. Adiwiyata school is expected to be agents of change for the people in the neighborhood around the school. Schools should be a model in creating a healthy and comfortable environment as well as being a model in creating a school community that cares and cultured environment. School community then expected to be an example and transmit characters care about the environment to the public. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i1.1661